Toward sutureless laparoscopic inguinal hernia repair in children? - Antonio Marte; Laura De Rosa; Lucia Pintozzi; Vincenzo Esposito (PAGEPress Publications, 2019)
We report our experience with a sutureless technique for laparoscopic inguinal hernia repair in children. Twenty-eight children, 12 girls and 16 boys, aged 3 months to 7 years, underwent sutureless laparoscopic inguinal hernia repair. In girls, we utilized simple cauterization of the internal inguinal ring with a single trocar technique. In boys denudation of the peritoneum was obtained utilizing a three-trocar technique. The peritoneum around the internal inguinal ring was peeled off and detached from the vas and the vessels, and then wrapped around the grasper, resulting in a large area of denudation. No perioperative complications were observed. No recurrences nor testicular damage were noted after a mean follow-up of 18 months (range 6-35 months). The mean operative time was 12 min (range 7-20 min) for girls and 19 min (range 15-30 min) for boys. A 6-year-old girl exhibited a lymphocele. The sutureless technique appears to be easy, safe, and effective, provided that the patients are carefully selected. In boys, special attention needs to be paid to preservation of the vas and the testicular vessels.